Non-destructive evaluation of nano silica-modified roller-compacted rubbercrete using combined SonReb and response surface methodology - Mohammed, B.S. (Taylor and Francis Ltd., 2018)
Roller-compacted concrete (RCC) is being widely used in highway construction industry (for pavement applications) due to its enormous advantages over conventional concrete rigid pavement. However, the major problems related to RCC pavement are the rigidity and relative tendency to crack due to low tensile strength. To address this problem, crumb rubber (CR) can be added as partial replacement of fine aggregate. High elastic and deformation properties of CR will increase the ductility of RCC pavement to absorb the deformation and strain energy caused by traffic loads. However, incorporating CR to RCC pavement leads to a reduction in mechanical properties which needs to be addressed for proper utilisation. Therefore, in this study, roller-compacted rubbercrete (RCR) was produced by partially replacing fine aggregate with CR. Nano silica was used as an additive to cement to mitigate the loss of mechanical properties in RCR caused by incorporation of CR. The non-destructive tests, that is, rebound hammer test and ultrasonic pulse velocity (UPV) were used to evaluate the performance of RCR. Response surface methodology was then used to develop models for predicting the 28 days UPV and rebound number (RN) of RCR. Combined UPVâRN (SonReb) models for predicting the 28 days strength of RCR based on combining UPV and RN were developed using multivariable regression (double power, bilinear, and double exponential models). From the combined SonReb models formulated, it is concluded that the double exponential model has better accuracy for predicting the 28 days compressive strength of RCR compared to the double power models recommended by RILEM 43-CND for conventional concrete. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group